2007
DOI: 10.2298/jsc0710953k
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in cuttings of Robinia pseudoacacia after treatment with naphthenate

Abstract: Naphthenic acids were isolated from gas oil fractions (distillation interval 168-290 qC) of Vojvodina crude oil "Velebit", characterized and their biological activity evaluated by the biochemical changes in cuttings of Robinia pseudoacacia after treatment with naphthenate. The activities of IAA peroxidase, total peroxidases and amylase, as well as the contents of reducing sugars and total proteins, were determined in the basal parts of soft wood cuttings of black locust after treatment with sodium naphthenate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…The concentrations of K-naph used in this study (0.1, 1 and 10 μM), were by 10 and 100 times higher compared to the concentration used in our previous studies [18,20,21,26], but were much lower than the concentrations used in phytotoxicity studies [27,28].…”
Section: Plant Materials and Treatment With Potassium Naphthenatecontrasting
confidence: 54%
See 1 more Smart Citation
“…The concentrations of K-naph used in this study (0.1, 1 and 10 μM), were by 10 and 100 times higher compared to the concentration used in our previous studies [18,20,21,26], but were much lower than the concentrations used in phytotoxicity studies [27,28].…”
Section: Plant Materials and Treatment With Potassium Naphthenatecontrasting
confidence: 54%
“…Studies of our group have shown that these substances influence plant rooting [18][19][20], as well as the accumulation of particular ions in the root and aboveground parts of plants [21]. The aim of the present work was to study the effect of the three low concentrations of potassium naphthenate (K-naph) (0.1, 1 and 10 μM) in two application modes (through the root and through the leaves) on the total antioxidant capacity and particular parameters of the antioxidant status of cucumber plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their widespread commercial uses [30], they are also prevalent in refinery process wastewater, which is the source of NAs contamination in the environment. It has been reported [31][32][33][34] that natural mixtures of NAs exhibit physiological activity similar to plant hormones of the auxin and gibberelin type. These carboxylic acids stimulate the rooting of cuttings and the lateral branches of sunflower [35], as well as poplar hardwood cuttings [36].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to form adventitious roots is affected by genotype, stock plants, types of cuttings, collection date, and endogenous factors related to cutting (Kibber et al, 2004;Tworkoski & Takeda, 2007). Numerous studies on adventitious root formation have shown that changes in phenolic compounds, sugar and protein content significantly affect root formation (Kaur et al, 2002;Sivaci & Yalcim, 2006;Kevresan et al, 2007;Satish et al, 2008). Carbohydrates are the direct products of photosynthesis; they serve as an energy source and provide the carbon necessary for production of new tissue (Sivaci & Yalcim, 2006).…”
mentioning
confidence: 99%
“…PPO is involved in the oxidation of phenol and contributes energy for cell division and cell differentiation in organogenesis of explants in tissue cultures (Satisha et al, 2008). Peroxidase is a marker of the inductive and initiative phases of root formation in plants (Yilmaz et al, 2003;Kevresan et al, 2007).…”
mentioning
confidence: 99%